Sustainable Bio-Dyeing of Cellulosic-Based Fabrics with Anthocyanins from Black Carrot (Daucus carota L.) - PARS, ABDULKADİR (My University, 2024)
In this study, anthocyanin-based black carrot (Daucus carota L.) extract was investigated as a natural textile dye on cellulosebased flax and cotton. Sodium alginate and gall oak (Quercus infectoria Olivier) were used as bio-mordants. The optimal dyeing conditions were determined by varying the amounts of these organic bio-mordants. A CIEL*a*b* spectrophotometer was used to measure the color characteristics of the dyed samples. The RP-HPLC-DAD method was used to identify the dye components in all dyed fabrics. Moreover, the dyed fabrics were evaluated for color fastness to washing, light, and rubbing. The mixture of these bio-mordants gave good color efficiency and acceptable colorfastness test results. Consequently, it appeared that black carrot (Daucus carota L.) can be used to color natural fibers. Applying these natural dye sources and bio-mordants may easily produce various colors. Keywords: Sustainability, flax, cotton, natural dyes, bio-mordants, HPLC (DAD), CIEL*a*b*.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); Sustainability; flax; cotton; natural dyes; bio-mordants; HPLC (DAD); CIEL*a*b*